Exaggerated sexual swellings and male mate choice in primates: testing the reliable indicator hypothesis in the Amboseli baboons. (June 2015) - Fitzpatrick, Courtney L.; Altmann, Jeanne; Alberts, Susan C.
Abstract : The paradigm of competitive males vying to influence female mate choice has been repeatedly upheld, but, increasingly, studies also report competitive females and choosy males. One female trait that is commonly proposed to influence male mate choice is the exaggerated sexual swelling displayed by females of many Old World primate species. The reliable indicator hypothesis posits that females use the exaggerated swellings to compete for access to mates, and that the swellings advertise variation in female fitness. We tested the two main predictions of this hypothesis in a wild population of baboons ( Papio cynocephalus ). First, we examined the effect of swelling size on the probability of mate guarding ('consortship') by the highest-ranking male and the behaviour of those males that trailed consortships ('follower males'). Second, we asked whether a female's swelling size predicted several fitness measures. We found that high-ranking males did not prefer females with larger swellings (when controlling for cycle number and conception) and that females with larger swellings did not have higher reproductive success. Our study, the only complete test of the reliable indicator hypothesis in a primate population, rejects the idea that female baboons compete for mates by advertising heritable fitness differences. Furthermore, we found unambiguous evidence that males biased their mating decisions in favour of females who had experienced more sexual cycles since their most recent pregnancy. Thus, rather than tracking the potential differences in fitness between females, male baboons appear to track and target the potential for a given reproductive opportunity to result in fertilization. Highlights: We examined the function and evolution of sexual swellings in female baboons. A common hypothesis predicts that females with larger swellings are higher quality. Consequently, males should prefer them as mates. Neither prediction held in our data. Instead, males attend to the likelihood of conception more than swelling size.